Molecular Characteristics of Giant Gourami from Ciamis and Banyumas - NURYANTO, Agus (Biospecies, 2018)
Giant gourami has been widely cultivated across Java Island, including in Banyumas and Ciamis Regencies. However, information genetic characters of both populations were not available. Therefore, this study aims to evaluate molecular characteristics of giant gourami from Ciamis and Banyumas. A purposive random sampling was done Molecular characterization was performed using randomly amplified polymorphic DNA. Molecular data were analyzed statisticaly. Both populations were genetically different and they have high genetic diversity within population. Based on the high genetic diversity of giant gourami from Ciamis and Banyumas populations, it would be very good to crossbreed between those both to produce high quality offspring.